2003
DOI: 10.1046/j.1365-2141.2003.04342.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional inhibitory human leucocyte antigen class I receptors on natural killer (NK) cells in patients with chronic NK lymphocytosis

Abstract: Summary. Chronic natural killer (NK) lymphocytosis is a rare disorder characterized by an indolent clinical course. Despite high NK cell numbers, many patients present with only mild clinical symptoms, and are often asymptomatic. NK cells are equipped with a range of receptors that bind human leucocyte antigen (HLA)-class I molecules. The killer immunoglobulin-like receptors (KIR, CD158) bind groups of HLA alleles, the CD94/NKG2 receptors bind HLA-E, and the CD85j (ILT2, LIR-1) receptor binds to the relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
(66 reference statements)
2
8
0
Order By: Relevance
“…Previous studies have also demonstrated that NK cells of LDGL patients express restricted NKRs (analysed by a panel of NKR monoclonal antibodies), and their results suggest that this correlates with monoclonal or oligoclonal NK cell expansion (Hoffmann et al , 2000; Mori et al , 2001; Morice et al , 2003; Warren et al , 2003). In the present study, CD94 expression was observed in all NK‐LDGL patients, whereas CD161 and KIR expression was observed in limited numbers of patients.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have also demonstrated that NK cells of LDGL patients express restricted NKRs (analysed by a panel of NKR monoclonal antibodies), and their results suggest that this correlates with monoclonal or oligoclonal NK cell expansion (Hoffmann et al , 2000; Mori et al , 2001; Morice et al , 2003; Warren et al , 2003). In the present study, CD94 expression was observed in all NK‐LDGL patients, whereas CD161 and KIR expression was observed in limited numbers of patients.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, autoimmune manifestations are not frequent in these patients. Several studies suggest that the fail-safe mechanism in LDGL patients could be represented by the expression of inhibitory receptors such as CD94/NKG2A [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…CD56 + NK cells have been known to represent a highly specialized lymphoid population characterized by a potent cytolytic activity against tumor or virally infected cells [32]. Compared to healthy controls, the cytotoxicity of NK cells decreases in peripheral blood of patients with various types of cancer [33].…”
Section: Resultsmentioning
confidence: 99%